Pengaruh Muhadharah Terhadap Kemampuan Public Speaking di Pondok Pesantren Cendekia Amanah - Fira Deyanti; Hindun Hindun (Pusat Riset dan Inovasi Nasional, 2024)
Public Speaking is the activity of speaking to a person or group of people. Through speaking activities, a person can convey ideas, thoughts and the contents of his heart to other people. The problem here is, not everyone can speak well, especially speaking in front of many people. In this research, we will discuss efforts to improve public speaking skills through muhadharah activities. This research aims to inspire many schools to hold muhadharah activities to improve students' public speaking skills. The background of this research is based on the fact that public speaking is something that needs to be mastered, but many people are actually afraid of this activity because they cannot control their feelings of nervousness, fear and embarrassment. Through qualitative methods, this research was conducted using data obtained from the Scholar Amanah students.